2002
DOI: 10.1182/blood-2002-06-1674
|View full text |Cite
|
Sign up to set email alerts
|

Deep-vein thrombosis in patients with multiple myeloma receiving first-line thalidomide-dexamethasone therapy

Abstract: consequently in many plasma pools. 2 More refined products (eg, albumin) were, however, consistently TTV-negative. 2,3 These findings confirm longstanding experience, derived from numerous viral validation studies, of the Cohn HSA manufacturing process as one with a high capacity for removing viruses. The explanation for the recent unexpected findings 1 thus remains enigmatic. Using the same 2 TTV primer sets and a third independent in-house primer system, we confirmed earlier reports 2,3 from research groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(90 citation statements)
references
References 7 publications
1
86
0
3
Order By: Relevance
“…This notion is supported by the combined analysis of published data, including our own study, on thalidomide combinations with or without doxorubicin, as shown in Table V. Irrespective of the particular combination therapy, the risk of venous thromboembolism in multiple myeloma seems to be enhanced during the early course of induction therapy, a phenomenon that may relate to tumour burden and tumour cell reduction (Cavo et al, 2002;Zangari et al, 2002b). In line with this hypothesis, four of the five venous thromboembolic events observed in the present study occurred during the first or second treatment cycle in responding patients.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This notion is supported by the combined analysis of published data, including our own study, on thalidomide combinations with or without doxorubicin, as shown in Table V. Irrespective of the particular combination therapy, the risk of venous thromboembolism in multiple myeloma seems to be enhanced during the early course of induction therapy, a phenomenon that may relate to tumour burden and tumour cell reduction (Cavo et al, 2002;Zangari et al, 2002b). In line with this hypothesis, four of the five venous thromboembolic events observed in the present study occurred during the first or second treatment cycle in responding patients.…”
Section: Discussionsupporting
confidence: 59%
“…In line with this hypothesis, four of the five venous thromboembolic events observed in the present study occurred during the first or second treatment cycle in responding patients. Importantly, the thrombotic risk seems to be linked to the disease and its treatment, rather than to pre-existing thrombophilic risk factors (Cavo et al, 2002;Zangari et al, 2002b). This conclusion would at least appear to be true for HyperCDT therapy as none of four patients with venous thromboembolism who were tested for thrombophilic abnormalities had evidence of natural anticoagulant deficiencies, antiphospholipid antibodies, activated protein C resistance, or factor V Leiden and prothrombin 20210 mutations respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This complication has been described in 3-5% of patients treated with thalidomide alone, 11 but it appears to be significantly more frequent when thalidomide is associated with dexamethasone or chemotherapy (21-28%). [50][51][52][53] Thus, the incidence of DVT registered in our series (7%) is relatively low, and could be considered as another advantage of this oral regimen.…”
Section: Discussionmentioning
confidence: 97%
“…6,7 Others have tried fixed low-dose warfarin as VTE prophylaxis but reported conflicting results. Zamagni et al used 1.25 mg warfarin daily and demonstrated a decrease in VTE incidence of 26-9% when treating de novo MM patients with dexamethasone and thalidomide.…”
Section: To the Editormentioning
confidence: 99%
“…2,3 Recently, several reports demonstrated that cytotoxic T lymphocytes (CTLs) specific for survivin-derived determinants are capable of efficiently killing leukemia targets endogenously expressing survivin. [3][4][5][6][7] In the current study, we identified a new HLA-A2-binding epitope, survivin [5][6][7][8][9][10][11][12][13][14] (TLPPAWQPFL). Using the T2 cellbinding assay, we found that survivin [5][6][7][8][9][10][11][12][13][14] showed comparable binding activity as the positive control peptide FluM1 58-66 (GILGFVFTL, data not shown).…”
Section: Figurementioning
confidence: 99%